Procedimiento de enseñanza de la matemática en estudiantes del primer grado de educación secundaria y su relación con el aprendizaje en instituciones educativas del distrito de San Juan - 2009 - Pongo Mendo, Enrique Gabriel (2013)
The Mathematics Program, this innovative method is based on the basis that mathematics is and should be the result of human activity. Consequently, the development of mathematical knowledge must begin with concrete experiences and, as abstractions are learned throughout secondary education, physical objects will be eliminated depending on the progress of each student. While conversation, interaction with classmates and the teacher will help learning and the development of information. You will be able to solve the problems that arise through the use of preliminary solutions, the comparison of results, the application of some procedures or the conceptualization of mathematics itself through the confrontation of points of view based on concrete experiences. The study will be collected in one go using an instrument applied to mathematics teachers of the first grade of secondary school at the educational institutions of San Juan. The type of research is correlational-transversal, since it aims to relate the variable teaching process with student learning. The level is very high in 67% of the results, but these figures differ depending on the elements of teaching and learning development detailed in the results.